Open and Calm – A randomized controlled trial evaluating a public stress reduction program in Denmark. (December 2015) - Jensen, Christian; Lansner, Jon; Petersen, Anders; Vangkilde, Signe; Ringkøbing, Signe; Frokjaer, Vibe; Adamsen, Dea; Knudsen, Gitte; Denninger, John; Hasselbalch, Steen
Abstract Background Prolonged psychological stress is a risk factor for illness and constitutes an increasing public health challenge creating a need to develop public interventions specifically targeting stress and promoting mental health. The present randomized controlled trial evaluated health effects of a novel program: Relaxation-Response-based Mental Health Promotion (RR-MHP). Methods The multimodal, meditation-based course was publicly entitled "Open and Calm" (OC) because it consistently trained relaxed and receptive ("Open") attention, and consciously non-intervening ("Calm") witnessing, in two standardized formats (individual or group) over nine weeks. Seventy-two participants who complained to their general practitioner about reduced daily functioning due to prolonged stress or who responded to an online health survey on stress were randomly assigned to OC formats or treatment as usual, involving e.g., unstandardized consultations with their general practitioner. Outcomes included perceived stress, depressive symptoms, quality of life, sleep disturbances, mental health, salivary cortisol, and visual perception. Control variables comprised a genetic stress-resiliency factor (serotonergic transporter genotype; 5-HTTLPR), demographics, personality, self-reported inattentiveness, and course format. Results Intent-to-treat analyses showed significantly larger improvements in OC than in controls on all outcomes. Treatment effects on self-reported outcomes were sustained after 3 months and were not related to age, gender, education, or course format. The dropout rate was only 6 %. Conclusions The standardized OC program reduced stress and improved mental health for a period of 3 months. Further testing of the OC program for public mental health promotion and reduction of stress-related illnesses is therefore warranted. A larger implementation is in progress. Trial registration: ClinicalTrials.gov.: NCT02140307. Registered May 14 2014.